Dietary microbiota-mediated shifts in gut microbial ecology and pathogen interactions in giant pandas (Ailuropoda melanoleuca) - Zheng Yan; Ying Yao; Qin Xu; Xin He; Xinyu Zhou; Hairui Wang (Communications Biology)
Abstract The impact of dietary microorganisms on host microbiota is recognized, but the underlying mechanisms remain unclear. This study examined the effects of bamboo surface microbiota, including virulence factors, antibiotic resistance genes (ARGs), and mobile genetic elements from different bamboo parts (leaves, shoots, and culms), on giant panda gut microbiota using three pairs of twins. Results showed that bamboo and fecal samples shared 1670 microbial species, with shoot surface microbiota contributing the highest proportion (21%, Bayesian source tracking) of contemporaneous gut microbiota, primarily by increasing abundances of Escherichia coli and ARGs. Klebsiella pneumoniae and Salmonella enterica also showed high co-occurrence in both bamboo and fecal samples, indicating potential colonization. Additionally, Streptococcus suis, Acinetobacter, and Mycobacterium progressively declined in fecal samples as bamboo shoot intake increased, suggesting these microbes are likely transient. The findings emphasize the impact of foodborne microorganisms on the host and the importance of conservation management.